The N-heterocyclic carbene-catalyzed [3 + 2] annulation of isoindigos with enals: the enantioselective construction of three contiguous stereogenic centers. Issue 13 (25th May 2022) - Liu, Binghao; Qi, Jing; Wu, Yatong; Li, Jia-Hui; Li, Yanting; Duan, Xiao-Yong
Abstract : An NHC-catalyzed enantioselective [3 + 2] annulation of enals and isoindigo is introduced as an efficient strategy for the construction of dimeric spirocyclic bisindoline alkaloid derivatives with moderate yields and good enantioselectivities. Abstract : Constructing contiguous all-carbon quaternary stereogenic centers has posed a long-standing synthetic challenge in organic chemistry. In this work, the NHC-catalyzed enantioselective [3 + 2] annulation of enals with isoindigo was introduced as an efficient strategy for the construction of dimeric spirocyclic bisindoline alkaloid derivatives with moderate yields and good enantioselectivities. Remarkably, three contiguous stereogenic centers—including two congested all-carbon quaternary stereogenic centers—were successfully constructed in a simple one-step operation.